Collaborative Governance in Accelerating MSME Adaptation in Facing the Era of the Industrial Revolution 4.0 in DIY - Nur Faidati; Nur Fitri Mutmainah (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2020)
This study intends to examine the scope of collaboration in strengthening the position of small and medium businesses in facing the 4.0 industrial revolution in the DIY region. The research question is How the collaboration process takes place in assisting the adaptation process of MSME actors facing the DIY industrial revolution era?. For this purpose, intrinsic case study research was conducted using a qualitative approach. The data collection techniques used in this study are literature studies and interviews. Collaboration formed in this context is realized by organizing several activities from each stakeholder. Collaborative governance in this context is carried out by involving several stakeholders, including the Office of Cooperatives and MSMEs at the Provincial, Regency or City level, the District Trade Office, business associations at the Subdistrict, Regency / City. The Collaborative Governance Process in the development of MSMEs in DIY during the era of the industrial revolution 4.0 has not implemented, because there are still overlapping programs and target groups.